ANALYSIS OF INTERNAL AND EXTERNAL CONFLICTS MAIN CHARACTER’S IN THE NOVEL "TWILIGHT SAGA: NEW MOON" BY STEPHENIE MEYER - Serly Rina Karmila; Eusabinus Bunau; Eni Rosnija (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of this research is to find out internal and external conflicts of the main character’s in the novel "Twilight Saga New Moon" by Stephenie Meyer that can be useful in building students and teachers’ good character’s specifically for English students of FKIP Untan. The method of this research is Descriptive Research. The novel consist 24 chapters and 563 pages. The methods that have been used and it was conducted in five stages, namely: (1) Characterization : who is the main character’s in the novel “Twilight Saga: New Moon by Stephenie Meyer, (2) Incident and interactions: what happens in the story with whom she interacts conflicts novel (3) The place: where the story takes place,(4) Time: when the story happened on the main character, (5) Theme: what are the themes in the story. The results showed that the main character has a unique character who is attracted to Edward. She knew the risks were enormous, very dangerous, but she was desperate for what she wanted. The conclusion is to give the reader an overview through Bella's experience of social life, how to prioritize attention to others, affection, love, and even friendship.Keywords: Twilight Saga New Moon, Main Character’s, Love and Friendship.